Optimizing the Function of Zakat in the Development of Micro, Small and Medium Enterprises and Alleviating Poverty: A Case Study at the National Zakat Agency of Sidenreng Rappang Regency - Saifullah Saifullah; Muhammad Ikbal; Ahmad Mustanir; Muhammad Abduh (Universitas Muslim Indonesia, 2022)
Zakat as a means of raising funds can be used productively for the development of MSMEs. The number of compulsory zakat in Sidrap district is more than one hundred thousand people. This potential can be used to alleviate poverty and improve community welfare. Departing from the above, the purpose of this research is to determine the potential of zakat in Sidenreng Rappang Regency, the development of MSMEs through zakat funds and increase the welfare of the community who receive zakat. The urgency of this research is an effort to optimize the use of zakat in the development of MSMEs and poverty alleviation in Sidenreng Rappang Regency. The method used in this research is a qualitative method through three stages, namely the invention, discovery, and explanation stages and the data collection techniques using in-depth interviews. Based on the results of the study, it was found that the amount of zakat collected at the Zakat Agency of Sidrap Regency during 2020 was Rp. 1,044,526,024 and donations of Rp. 1,199,318,100. Zakat and donations are distributed through several programs according to their respective asnaf, namely the needy, 15%, 20% poor, 12.5% Amil, 7.5% converts, 2.5% shackled people, people owing 10% 20%, people who struggle in the path of Allah and foreigners who do not have the cost to return to their place of origin 12.5%. Apart from being intended for the asnaf-asnaf above, the results of the Baznas collection are also intended for social assistance through several programs such as education assistance (smart sidrap), independent sidrap (empowerment assistance for small entrepreneurs), fire assistance, and basic food assistance.